University Students’ Perceptions of Gamification in English Language Learning - Randila Tiayu Ismar; Endah Anisa Rahma (English Education Journal: Jurnal Pengembangan Pendidikan dan Pengembangan Pengajaran Bahasa, 2025)
This study aims to explore university students’ perceptions of gamification in English language learning. With the growing integration of digital tools in education, understanding learners’ responses to gamified instruction is essential to ensure its effectiveness. Conducted at Universitas Teuku Umar, this research involved 93 second-semester students from four different academic programs who had prior exposure to gamified learning platforms such as Kahoot and Quizziz. The study employed a descriptive quantitative methodology, utilizing a structured Likert-scale questionnaire consisting of 20 items categorized into five dimensions: feelings, classroom atmosphere, engagement, motivation, and comprehension. Data were analyzed using descriptive statistics, including mean, standard deviation, and percentage of agreement. The findings indicate that students generally hold moderately positive perceptions of gamification. The highest mean scores were observed in items related to enjoyment, interest in classroom activities, and motivation to learn. However, some neutral responses emerged in areas concerning distraction, competitiveness, and clarity of learning objectives. These suggest that while gamification enhances engagement and enjoyment, it must be implemented carefully to maintain focus on academic outcomes. This study implies that gamification, when used strategically, has the potential to foster a more engaging and motivating language learning environment. Further research is recommended to explore the long-term effects of gamification and its impact on different learner profiles.